Fusobacterium nucleatumin Colorectal Carcinoma Tissue According to Tumor Location. Issue 11 (November 2016) - Mima, Kosuke; Cao, Yin; Chan, Andrew T; Qian, Zhi Rong; Nowak, Jonathan A; Masugi, Yohei; Shi, Yan; Song, Mingyang; da Silva, Annacarolina; Gu, Mancang; Li, Wanwan; Hamada, Tsuyoshi; et al.
Abstract : OBJECTIVES: : Evidence suggests a possible role of Fusobacterium nucleatum in colorectal carcinogenesis, especially in right‐sided proximal colorectum. Considering a change in bowel contents and microbiome from proximal to distal colorectal segments, we hypothesized that the proportion of colorectal carcinoma enriched with F. nucleatum might gradually increase along the bowel subsites from rectum to cecum. METHODS: : A retrospective, cross‐sectional analysis was conducted on 1, 102 colon and rectal carcinomas in molecular pathological epidemiology databases of the Nurses' Health Study and the Health Professionals Follow‐up Study. We measured the amount of F. nucleatum DNA in colorectal tumor tissue using a quantitative PCR assay and equally dichotomized F. nucleatum ‐positive cases (high vs. low). We used multivariable logistic regression analysis to examine the relationship of a bowel subsite variable (rectum, rectosigmoid junction, sigmoid colon, descending colon, splenic flexure, transverse colon, hepatic flexure, ascending colon, and cecum) with the amount of F. nucleatum . RESULTS: : The proportion of F. nucleatum ‐high colorectal cancers gradually increased from rectal cancers (2.5%; 4/157) to cecal cancers (11%; 19/178), with a statistically significant linear trend along all subsites ( P <0.0001) and little evidence of non‐linearity. The proportion of F. nucleatum ‐low cancers was higher in rectal, ascending colon, and cecal cancers than in cancers of middle segments. CONCLUSIONS: : The proportion of F. nucleatum ‐high colorectal cancers gradually increases from rectum to cecum. Our data support the colorectal continuum model that reflects pathogenic influences of the gut microbiota on neoplastic and immune cells and challenges the prevailing two‐colon (proximal vs. distal) dichotomy paradigm.